Social motives of university students in seven countries: Measurement development and validation - Emiko, S. K.; Plusnin, N.; Ochoa, D. P.; Du, H.; Klackl, J.; Ah Gang, G. C.; Gan, S. W.; Siti, Nor Yaacob; Wu, Shin Ling *; Qumseya, T.; Nicolas, G.; Fiske, S. T. (Asian Association of Social Psychology / Wiley, 2021)
A new scale to measure core social motives was developed based on the BUC(K)ET framework (Belong, Understand, Control, Esteem, and Trust). The scale was completed by 1,516 university students from seven countries: Australia, the United States, New Zealand, the Philippines, Malaysia, China (Macao), and Austria. Multigroup confirmatory factor analysis supported the scale's full scalar invariance between Australia and the United States and between Australia and Austria. Partial scalar invariance was established for all countries after omitting the Understand motive, suggesting that the remaining four subscales can be used to compare levels of social motives across diverse cultural groups with caution. We further established the scale's construct validity by examining its correlations in the nomological networks involving several individual difference variables. The profile of social motives was remarkably similar across countries and gender groups, although three Asian groups showed higher motives to belong than non-Asian groups, and women showed generally stronger core social motives than men, especially the Belong motive. Implications and possible directions of research are discussed.